A surgical mouse model of neonatal pressure overload by transverse aortic constriction - Malek Mohammadi, Mona; Abouissa, Aya; Heineke, Jörg (Nature protocols, 2021)
Cardiac disease is the main cause of death worldwide. Insufficient regeneration of the adult mammalian heart is a major driver of cardiac morbidity and mortality. Cardiac regeneration occurs in early postnatal mice, thus understanding mechanisms of mammalian cardiac regeneration could facilitate the development of novel therapeutic strategies. Here, we provide a detailed description of a neonatal mouse model of pressure overload by transverse aortic constriction (nTAC) that can be applied at postnatal days 1 and 7. We have previously used this model to demonstrate that mice are able to fully adapt to pressure overload following nTAC on postnatal day 1. In contrast, when nTAC is applied in the non-regenerative phase (at postnatal day 7), it is associated with a maladaptive response similar to that seen when transverse aortic constriction (TAC) is applied to adult mice. Once a user is experienced in nTAC surgery, the procedure can be completed in less than 10 min per mouse. We anticipate that this model will facilitate the discovery of therapeutic targets to treat patients or prevent pressure overload-induced cardiac failure in the future.